2012
DOI: 10.1021/jp3009699
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Arginine Formations in Protein Function and Assembly: Rings, Strings, and Stacks

Abstract: Protein-protein interfaces are often stabilized by a small number of dominant contacts, exemplified by the overrepresentation of arginine residues at oligomerization interfaces. Positively charged arginines are most commonly involved in ion pairs of opposite charge; however, previous work of Scheraga and coworkers described the stable, close range interaction between guanidinium pairs in a solvated environment. To extend this work, we searched over 70 thousand protein structures and complexes for unusual forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
83
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(92 citation statements)
references
References 56 publications
9
83
0
Order By: Relevance
“…Instead, R1948 of the mutant kinase reorients toward the ATP binding site, forming an unusual ion-pair with R2032 that restricts P-loop flexibility. This interaction, although uncommon, has also been observed in other proteins as a stabilizing factor (26)(27)(28).…”
Section: Resultsmentioning
confidence: 56%
“…Instead, R1948 of the mutant kinase reorients toward the ATP binding site, forming an unusual ion-pair with R2032 that restricts P-loop flexibility. This interaction, although uncommon, has also been observed in other proteins as a stabilizing factor (26)(27)(28).…”
Section: Resultsmentioning
confidence: 56%
“…The interface is largely composed of electrostatic interactions between charged residues from a loop, and the interface has a buried surface area of 1,184.1 Å 2 (Figure 3B). Additionally, the guanidinium groups from a pair of Arg169 residues from α-helix number 2 adopt a planar stacking conformation (Neves et al, 2012), and their interaction is bridged through hydrogen bonds with a sulfate group. The interaction surface of MiD51 is distinct from that of other NTase family members known to dimerize.…”
Section: Resultsmentioning
confidence: 99%
“…Although this is the first arginine pairing observed in GPCRs, arginine-arginine short-range interactions are found in many other proteins, where these residues are involved in binding of nucleotides, organic acids and other negatively charged bioactive molecules. From analysis of 67,520 crystal structures containing clusters of positively charged arginines, Neves and colleagues (Neves et al 2012) demonstrated that guanidium groups tend to sit in polar pockets or are exposed to solvent. In a much earlier study, computer simulations of Magalhaes and colleagues (Magalhaes et al 1994) have predicted the importance of solvent environment for arginine pairing.…”
Section: X-ray Crystallography Of Ffa1mentioning
confidence: 99%